Análisis económico del derecho aplicado a la enseñanza del Derecho : Una aproximación al uso de la Teoría de Juegos. (2018)
The Economic Analysis of Law Applied to the Teaching of Law (AED) has raised itself in the faculties of law particularly in the investigative field, as an important tool for the boarding transformation and comprehension of the juridical structures from the efficiency in economic terms, it constitutes little more than an application of the methods and concepts of the economy science with the purpose of analyzing the juridical institutions from the efficiency, it is to say from the effects of the norm in the society, more than from the process of creation or his relation with the justice. A tool used from the economy is the game theory, whose mayor attractive would reside in the possibility of being applied to the analysis of the behavior of the individuals who interact in a society with prescriptive purposes; in conformity with which the present work chases to demonstrate the utility of this tool to the interior of the educational processes of the right, with a view to improving the comprehension of the juridical institutions, his functionality and his importance.